Phosphorylation of Yeast Pah1 Phosphatidate Phosphatase by Casein Kinase II Regulates Its Function in Lipid Metabolism - Hsieh, Lu-Sheng; Su, Wen-Min; Han, Gil-Soo; Carman, George M. (The Journal of biological chemistry, 2016)
Pah1 phosphatidate phosphatase in Saccharomyces cerevisiae catalyzes the penultimate step in the synthesis of triacylglycerol (i.e. the production of diacylglycerol by dephosphorylation of phosphatidate). The enzyme playing a major role in lipid metabolism is subject to phosphorylation (e.g. by Pho85-Pho80, Cdc28-cyclin B, and protein kinases A and C) and dephosphorylation (e.g. by Nem1-Spo7) that regulate its cellular location, catalytic activity, and stability/degradation. In this work, we show that Pah1 is a substrate for casein kinase II (CKII); its phosphorylation was time- and dose-dependent and was dependent on the concentrations of Pah1 (Km = 0.23 μm) and ATP (Km = 5.5 μm). By mass spectrometry, truncation analysis, site-directed mutagenesis, phosphopeptide mapping, and phosphoamino acid analysis, we identified that >90% of its phosphorylation occurs on Thr-170, Ser-250, Ser-313, Ser-705, Ser-814, and Ser-818. The CKII-phosphorylated Pah1 was a substrate for the Nem1-Spo7 protein phosphatase and was degraded by the 20S proteasome. The prephosphorylation of Pah1 by protein kinase A or protein kinase C reduced its subsequent phosphorylation by CKII. The prephosphorylation of Pah1 by CKII reduced its subsequent phosphorylation by protein kinase A but not by protein kinase C. The expression of Pah1 with combined mutations of S705D and 7A, which mimic its phosphorylation by CKII and lack of phosphorylation by Pho85-Pho80, caused an increase in triacylglycerol content and lipid droplet number in cells expressing the Nem1-Spo7 phosphatase complex.